Overhead pressing power/strength movements - Waller, M.; Piper, T.; Miller, J. (Strength and Conditioning Journal, 2009)
The purpose of this article is to discuss the execution of overhead pressing movements from the shoulder press to the split jerk. There are numerous exercises and their variations have been used by individuals in their strength and conditioning programs for increasing upper extremity pressing strength. These require the upper extremities to generate the pressing force while using the lower extremity to generate a stabilizing force.